The Effect of Competitive Intelligence in Product & Service Innovation Using A Need Pull Modell - Nemutanzhela, Phathutshedzo (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This paper discusses the findings of the study that was aimed at establishing the effect of Competitive Intelligence, hereafter referred to as CI, on product and service innovations. A literature study revealed that CI and innovation are widely studied subjects, but the impact of CI on innovation was not well documented. CI has been widely acclaimed as a panacea to a lot of organizational problems. The study aimed at the innovative aspect. A descriptive study using both qualitative and quantitative methods was done on five companies. The paper presents a literature study, the methodology used, the findings and the model that was proposed that showed the process of how CI affects innovative process. Conclusions of the study basing on the findings are presented